Multi robot cooperative rescue based on two-stage task allocation algorithm. Issue 1 (1st October 2022) - Huang, Jie; Song, Quanjun; Xu, Zhannan
Abstract: Task allocation is an important issue in the decision-making of multi robot fire rescue in underground garage. In this paper, a multi robot and multi-objective optimization model is constructed. According to the real-time requirements of fire rescue in the underground garage scene, a two-stage multi robot task allocation algorithm based on ant colony and contract net protocol is proposed, which solves the global deficiency of the allocation result based on contract net protocol and the defect that ant colony optimization can not respond to environmental changes in real time. The comparative test results in dynamic environment show that the two-stage task allocation algorithm is similar to ant colony optimization in global cost, and its real-time performance is better than ant colony optimization.